Molecular characterization of Moniezia sichuanensis in captive musk deer (Moschus berezovskii). Issue 4 (19th July 2017) - Xu, J.; Lin, H.; Chen, J.; Cai, Y.; Fu, W.; Wang, H.; Gu, X.; Lai, W.; Peng, X.; Yang, G.
Abstract: The musk deer ( Moschus berezovskii ) is an economically important species from which musk is extracted and used in perfumes and medicines. Cestodes (parasitic flatworms) of the genus Moniezia are important parasites that infect this endangered species and can cause high mortality in young deer. In 1982, Moniezia (S.) sichuanensis sp. nov. was described from a specimen obtained from wild musk deer. The new species was distinct from the other described species of Moniezia by the sawtooth-shaped interproglottidal glands, the thick vagina and the absence of a cirrus spine. In the present study, 12 cestodes collected from musk deer were examined morphologically and confirmed to be M. s ichuanensis. Molecular characterization was performed by amplifying and comparing the internal transcribed spacer 1 (ITS1) and 5.8S rRNA gene (ITS1–5.8S) of ribosomal DNA with available sequences from other Moniezia species. The amplified sequences ranged from 761 to 764 bp and similarity ranged from 98.7–100%, compared to 67.8–92.4% with other Moniezia spp. Construction of a phylogenetic tree using the neighbour-joining method indicated that all 12 ITS1–5.8S sequences formed a single clade, confirming M. sichuanensis as a separate species. This study provides novel molecular insight into M. sichuanensis that could prove useful for future diagnosis and control of monieziasis in musk deer.